Staphylococcal Cassette Chromosome mec in MRSA, Taiwan - Jann-Tay Wang (Emerging Infectious Diseases, 2007)
To determine the predominant staphylococcal cassette chromosome (SCC) mec element in methicillin-resistant Staphylococcus aureus, we typed 190 isolates from a hospital in Taiwan. We found a shift from type IV to type III SCCmec element during 1992–2003, perhaps caused by selective pressure from indiscriminate use of antimicrobial drugs.